Effect of vitamin E in nonalcoholic fatty liver disease with metabolic syndrome: A propensity score-matched cohort study - Kim, Gi Hyun (Clin Mol Hepatol, 2015)
BACKGROUND/AIMS: Vitamin E improves the biochemical profiles and liver histology in nonalcoholic steatohepatitis, but the role of vitamin E is not clearly defined in the management of nonalcoholic fatty liver disease (NAFLD) which includes both simple steatosis and steatohepatitis. Co-morbid metabolic syndrome increases the probability of steatohepatitis in NAFLD. In this study, we aimed to determine the short-term effects of vitamin E and off-treatment durability of response in a propensity-score matched cohort of NAFLD patients with metabolic syndrome. METHODS: A retrospective cohort was constructed by retrieving 526 consecutive NAFLD patients from the electronic medical record data warehouse of a tertiary referral hospital in South Korea. Among them, 335 patients (63.7%) had metabolic syndrome and were eligible for vitamin E therapy. In order to assess the effect of vitamin E, propensity score matching was used by matching covariates between control patients (n=250) and patients who received vitamin E (n=85). RESULTS: The PS-matched vitamin E group (n=58) and control group (n=58) exhibited similar baseline metabolic profiles. After 6 months of vitamin E therapy, the mean ALT levels decreased significantly compared to PS-matched control (P<0.01). The changes in metabolic profiles (body weight, lipid and glucose levels) did not differ between control and vitamin E groups during the study period. CONCLUSIONS: Short-term vitamin E treatment significantly reduces ALT levels in NAFLD patients with metabolic syndrome, but metabolic profiles are not affected by vitamin E.